(untitled) (Heritage, 2022)
After a short war in April 1941 Kingdom of Yugoslavia was occupied by Axis forces. Soon after, in May 1941 small group of free Yugoslav army soldiers and officers under the leadership of Colonel Dragoljub Mihailović formed a resistance movement on mountain Suvobor, Ravna Gora plateau, in western Serbia. One of the main problems and tasks of the army, especially the resistance group, was establishing a system of internal and external communication. Yugoslav Army in the Homeland came up with the solutions for the organization of its communication system via communication systems of the pre-war Yugoslav army and the Ministry of foreign affairs. By the end of World War One and the creation of Yugoslavia, the country`s military created a system of internal communication which development depended on the economic situation in the country and its diplomatic relations with the great forces. The main difficulties for the Yugoslav Army in the Homeland radio-communication system were lack of equipment and materials for radio communication devices and a small number of people on occupied territory capable of using radio devices. Considering that this organization worked during the Axis occupation, counterintelligence operations of enemy armies, primarily German intelligence, made conducting successful operations even more complex for members of the Ravna Gora movement.